2019
DOI: 10.23938/assn.0745
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Communication Skills Scale in nursing professionals

Abstract: Fundamento. La Escala sobre Habilidades de Comunicación (EHC) es un instrumento para evaluar las habilidades de comunicación en diferentes profesionales sanitarios; sin embargo, no se ha realizado ni un análisis diferencial de sus propiedades psicométricas por profesiones, ni baremos específicos. Por ello, el objetivo del presente estudio fue analizar las propiedades psicométricas de la EHC y elaborar un baremo en profesionales de Enfermería. Material y Métodos. Estudio instrumental para analizar las propiedad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 19 publications
1
6
0
2
Order By: Relevance
“…However, fitting the data to the model required specification of a structure with correlated measures between items 16 ('I find it difficult to make requests of patients') and 18 ('I find it difficult to ask for information from the patients'). This change was suggested by the modification indices obtained after the confirmatory factor analysis and was previously reported in the study of health care professionals [21] as well as in the specific nursing professional sample [38]. In addition, it is important to note that both items had low factorial loads in their corresponding subscales and had also shown the lowest factorial loads in the other two validation studies.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…However, fitting the data to the model required specification of a structure with correlated measures between items 16 ('I find it difficult to make requests of patients') and 18 ('I find it difficult to ask for information from the patients'). This change was suggested by the modification indices obtained after the confirmatory factor analysis and was previously reported in the study of health care professionals [21] as well as in the specific nursing professional sample [38]. In addition, it is important to note that both items had low factorial loads in their corresponding subscales and had also shown the lowest factorial loads in the other two validation studies.…”
Section: Discussionsupporting
confidence: 65%
“…Confirmatory factorial analysis showed that the scale preserved the original structure proposed by Leal-Costa et al [38], and the fit indices were adequate. The HP-CSS comprised the four dimensions identified in the original article: Informative communication, Empathy, Respect, and Assertiveness.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…The Communication Skills Scale (CSS; Leal-Costa et al, 2016, Leal-Costa et al, 2019 was utilized to evaluate the communication skills of the nurses. This scale is composed of 18 items, with a Likert-type response scale, and was scored with a 6point frequency scale which indicated how often they performed the item.…”
Section: Instrumentsmentioning
confidence: 99%